Identity, place narrative and biophilic urban development: Connecting the past, present and future for sustainable liveable cities - O'Sullivan, Kate; Shirani, Fiona; Hale, Rachel; Pidgeon, Nick; Henwood, Karen (Frontiers in Sustainable Cities, 2023)
Urbanization presents sustainability challenges for the natural environment, resources and ecological systems, whilst high levels of pollution and disconnect from the natural environment can adversely impact the health and wellbeing of urban residents. Rapid urbanisation can also curtail processes of placemaking, including place attachment and place identity, raising questions around the social sustainability and liveability of cities into the future. With such concerns in mind, cities are increasingly called upon to develop in ways that are environmentally, socially, and economically sustainable. The concept of biophilia has been applied to sustainable urban development, in which nature and green infrastructure are systematically incorporated into cities to reduce adverse impacts to the natural environment while supporting the social, cultural and economic sustainability of communities. This paper explores findings from community focus groups centred on perceptions of a proposed biophilic urban development in Wales, UK. We highlight how community members understand and negotiate possible impacts the development may have on the city by drawing on their own emplaced experiences, as well as their perception of the city in relation to broader contexts of economic crisis and environmental change. We highlight the importance of temporally and spatially situated understandings of innovative building developments, as part of sustainable urban developments, and how such transformative processes should enable community place-making, and as such become valued, and sustained through time.